Book Review: S. GERMANIDOU (ed.), Secular Byzantine Women. Art, Archaeology, and Ethnography of Female Material Culture from Late Roman to Post - Byzantine Times, London and New York, Routledge, 2022 - ΣΟΛΩΜΟΥ, Σταυρούλα (Byzantina Symmeikta, 2022)
Book Review: S. GERMANIDOU (ed.), Secular Byzantine Women. Art, Archaeology, and Ethnography of Female Material Culture from Llate Roman to Post - Byzantine Times, London and New York, Routledge, 2022